Bone marrow lesions in knee osteoarthritis: regional differences in tibial subchondral bone microstructure and their association with cartilage degeneration. Issue 11 (November 2019) - Muratovic, D.; Findlay, D.M.; Cicuttini, F.M.; Wluka, A.E.; Lee, Y.R.; Edwards, S.; Kuliwaba, J.S.
Summary: Objective: The aim of this study was to investigate how bone microstructure within bone marrow lesions (BMLs) relates to the bone and cartilage across the whole human tibial plateau. Design: Thirty-two tibial plateaus from patients with osteoarthritis (OA) at total knee arthroplasty and eleven age-matched non-OA controls, were scanned ex vivo by MRI to identify BMLs and by micro CT to quantitate the subchondral (plate and trabecular) bone microstructure. For cartilage evaluation, specimens were processed histologically. Results: BMLs were detected in 75% of the OA samples (OA-BML), located predominantly in the anterior-medial (AM) region. In contrast to non-OA control and OA-no BML, in OA-BML differences in microstructure were significantly more evident between subregions. In OA-BML, the AM region contained the most prominent structural alterations. Between-group comparisons showed that the AM region of the OA-BML group had significantly higher histological degeneration (OARSI grade) ( P  < .0001, P  < .05), thicker subchondral plate ( P  < .05, P  < .05), trabeculae that are more anisotropic ( P  < .0001, P  < .05), well connected ( P  < .05, P  = n.s), and more plate-like ( P  < 0.05, P  < 0.05), compared to controls and OA-no BML at this site. Compared to controls, OA-no BML had significantly higher OARSI grade ( P  < .0001), and lower trabecular number ( P  < .05). Conclusion: In established knee OA, both the extent of cartilage damage and microstructural degeneration of the subchondral bone were dependent on the presence of a BML. In OA-no BML, bone microstructural alterations are consistent with a bone attrition phase of the disease. Thus, the use of BMLs as MRI image-based biomarkers appear to inform on the degenerative state within the osteochondral unit.